Aspects of writing knowledge and EFL students' writing quality - Rofiqoh Rofiqoh; Yazid Basthomi; Utami Widiati; Yunita Puspitasari; Saiful Marhaban; Teguh Sulistyo (Universitas Syiah Kuala, 2022)
Writing knowledge pertaining to process, system, content, and genre plays an essential role to produce an intelligible composition. The purpose of the present study is twofold – to investigate the correlation between aspects of writing knowledge and quality of writing, and to investigate the contribution of the overall and individual aspects of writing knowledge to writing quality. The participants were 54 second-year ELT undergraduate students of a university in Indonesia. A writing test and multiple-choice test on writing knowledge were used as the instruments of data collection. The analysis employed Pearson correlation coefficient and multiple regressions. The result revealed a significant positive correlation between writing knowledge and writing quality. As a unit, the knowledge of process, system, content, and genre, indicates a significant contribution to the writing quality. Individually, however, only process knowledge significantly contributes to the writing quality. It provides additional pieces of evidence that process knowledge be given special attention, thus writing instruction should allow students to learn writing knowledge explicitly and implicitly.